Highly crystalline carbon dots from fresh tomato: UV emission and quantum confinement. (7th November 2017) - Liu, Weijian; Li, Chun; Sun, Xiaobo; Pan, Wei; Yu, Guifeng; Wang, Jinping
Abstract: In this article, fresh tomatoes are explored as a low-cost source to prepare high-performance carbon dots by using microwave-assisted pyrolysis. Given that amino groups might act as nucleophiles for cleaving covalent bridging ester or ether in the crosslinked macromolecules in the biomass bulk, ethylenediamine (EDA) and urea with amino groups were applied as nucleophiles to modulate the chemical composites of the carbon nanoparticles in order to tune their fluorescence emission and enhance their quantum yields. Very interestingly, the carbon dots synthesized in the presence of urea had a highly crystalline nature, a low-degree amorphous surface and were smaller than 5 nm. Moreover, the doped N contributed to the formation of a cyclic form of core that resulted in a strong electron-withdrawing ability within the conjugated C plane. Therefore, this type of carbon dot exhibited marked quantum confinement, with the maximum fluorescence peak located in the UV region. Carbon nanoparticles greater than 20 nm in size, prepared using pristine fresh tomato and in the presence of EDA, emitted surface state controlled fluorescence. Additionally, carbon nanoparticles synthesized using fresh tomato pulp in the presence of EDA and urea were explored for bioimaging of plant pathogenic fungi and the detection of vanillin.